Assessing Institutional Practices and Conditions in the Development of Students in Ethiopian Sports Academies – Insiders’ Perspectives - Asmamaw (Ph.D), Aemero; Habtmariam (Ph.D.), Sirak; Tadesse (Ph.D.), Tefera (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2021)
The objective of this study was to assess the prevailing institutional practices and conditions in the overall development of students in Ethiopian Sports academies considering the insiders’ perspectives. To this end, the study used a qualitative case study design included two purposfully selected sports academies (Ethiopian Youth Sports Academy and Tirunesh Dibaba Sports Academy). In this two sports academies, the researchers conducted focus- group discussions with randomly selected sport academy students (n = 20), and interviewed two coaches and two directors (one from each academy). The findings of the study revealed that, most of the study participants believed that motivation, positive learning environment, adequecy of requiered resources and proper usie of time, effort, and peer support are found to be essential conditions that foster success and enhance performance in sports academy education. Furthermore, many of them explained some best institutional practices. For example, positive relationship with coaches, proper management of sporting events with the specified schedules, and conducting friendly games with various clubs. Apart from these, study participants identified some challenges that detter implementation of sports education in the academies. There are an exclusive focuse on the practical skills without supporting that by theoretical and other related psychological components. Also, the coaches arrange friendly matches with more advanced clubs that have senior players that did not match with the age cohorts of sports academy students. Moreover coaches trainings focus on team trainings than individual works, and there are scarce sports equipment and facilities, and lack of recreation centers in the immediate vicinity . It is obvious that these impendements have had negative influences on students physical , psychological enhancement and in the overall learnings and performances. Therefore, participants suggested several recommendations to allivate these and enhance the performance of sports acadmy students